Challenges and achievements in the utilization of the health system among adolescents in a region of Burkina Faso particularly affected by poverty - Krohn, Joshua; Bountogo, Mamadou; Ouermi, Lucienne; Sié, Ali; Bärnighausen, Till; Harling, Guy (BMC health services research, 2023)
Objective: Healthcare for adolescents receives little attention in low-income countries globally despite their large population share in these settings, the importance of disease prevention at these ages for later life outcomes and adolescent health needs differing from those of other ages. We therefore examined healthcare need and use among adolescents in rural Burkina Faso to identify reasons for use and gaps in provision and uptake. Methods: We interviewed 1,644 adolescents aged 12-20 living in rural northwestern Burkina Faso in 2017. Topics included healthcare need and satisfaction with care provided. We calculated response-weighted prevalence of perceived healthcare need and utilization, then conducted multivariable regression to look at predictors of need, realized access and successful utilization based on the Andersen and Aday model. Results: 43.7 [41.2 - 46.0] % of participants perceived need for healthcare at least once in the preceding 12 months - 52.0 [48.1 - 56.0] % of females and 35.6 [32.5 - 39.0] % of males. Of those with perceived need, 92.6 [90.0 - 94.3] % were able to access care and 79.0 [75.6 - 82.0] % obtained successful utilization. Need was most strongly predicted by gender, education and urbanicity, while predictors of successful use included household wealth and female guardian’s educational attainment. Conclusion: Healthcare utilization among adolescents is low in rural Burkina Faso, but mostly thought of as sufficient with very few individuals reporting need that was not linked to care. Future objective assessment of healthcare need could help identify whether our results reflect a well-functioning system for these adolescents, or one where barriers lead to low awareness of needs or low expectations for service provision.